PENGARUH INFLASI, NILAI TUKAR RUPIAH, DAN TINGKAT SUKU BUNGA TERHADAP INDEKS HARGA SAHAM - Safira Dewi Srikandi; Andri Syahputra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the effect of inflation, exchange rates, and interest rates on the stock price index. The population of this study is the consumer goods industry sector companies listed on Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research is a quantitative research with associative method. The data used in this research is secondary data. This research was conducted with the help of E-views. The research method used is multiple linear regression analysis of panel data. The results of this study showed that inflation and exchange rated affected the stock price index. While interest rates has no effect on stock price index